Development and validation of safety practices, perceived risk, risk coping and stigma questionnaire among frontline healthcare workers dealing with covid-19 pandemic in Hospital Universiti Sains Malaysia - How, Ooi Jun (2023)
Background: Healthcare workers (HCWs) are at higher risk of contracting COVID-19 infection compared to the general population. Safety practices, perceived risk, risk coping strategies and stigma faced by HCWs are important aspects to be investigated to ensure their wellbeing. This study aims to develop and validate Safety Practices, Perceived Risk, Risk Coping and Stigma Questionnaire among HCWs in Hospital Universiti Sains Malaysia (Hospital USM), Malaysia. Methods: The questionnaire was generated after an extensive literature review. Content validity was done by six experts, followed by face validity with eight HCWs from the Emergency Department, Hospital USM. A cross-sectional study was done among 213 frontline HCWs directly or indirectly involved in managing COVID-19 patients in Hospital USM. Exploratory factor analysis (EFA) and reliability analysis were done. Findings: Content validity was acceptable with item-level content validity index (I-CVI) ranging from 0.83 to 1.00 and scale-level content validity index (S-CVI) ranging from 0.85 to 1.00. Face validity was acceptable with item-level face validity index (I-FVI) ranging from 0.88 to 1.00 and scale-level face validity index (S-FVI) ranging from 0.85 to 1.00. For EFA, all factor loadings were more than 0.30. The safety practices domain was divided into three subdomains. The perceived risk domain showed three factors, the risk coping domain showed four factors, while the stigma domain revealed two factors. Cronbach’s alpha was acceptable (0.714-0.970) except for the factor dietary change under the risk coping domain which scored 0.479. Conclusions: The Safety Practices, Perceived Risk, Risk Coping and Stigma Questionnaire is valid. All domains of this questionnaire have good reliability, except for the factor dietary change under the risk coping domain. This validated questionnaire will thoroughly assess HCWs during the COVID-19 pandemic and guide policymakers to plan appropriate interventions if required.